2000
DOI: 10.1021/la000628n
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption States of NO2 over Water−Ice Films Formed on Au(111)

Abstract: The adsorption states of NO2 over amorphous and crystalline water-ice films formed on an Au(111) surface have been studied in an ultrahigh vacuum system by the temperature programmed desorption (TPD) technique and IR absorption-reflection spectroscopy (IRAS). The ice films are prepared by deposition of gas phase water on the Au substrate at <100 K for amorphous ice and at 140 K for crystalline ice. The surface of amorphous ice is characterized by the high density of free OH, while that of crystalline ice is ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
46
2

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(53 citation statements)
references
References 37 publications
5
46
2
Order By: Relevance
“…This exposure resulted in the formation of 500 monolayers ͑ML͒ of H 2 O on the substrate if we adopt the reported experimental conversion factor of 1 ML coverage deposition by 3 L exposure. 23 Unfocused 157 nm laser radiation with a full width at half maximum duration of 10 ns was incident at an angle of about 80°to the surface normal on the ice surface at a fluence Ͻ0.1 mJ cm −2 pulse −1 . O͑ 3 P J=2,1,0 ͒ atom products were subsequently ionized at a distance of 4 mm ͑2 mm for OH͒ from the substrate surface by the ͑2+1͒ REMPI transition via the O͑ 3 P J − 3 P J ͒ transition at 225.6-226.4 nm, 24 and collected with a small mass spectrometer aligned perpendicular to the ice surface.…”
Section: Methodsmentioning
confidence: 99%
“…This exposure resulted in the formation of 500 monolayers ͑ML͒ of H 2 O on the substrate if we adopt the reported experimental conversion factor of 1 ML coverage deposition by 3 L exposure. 23 Unfocused 157 nm laser radiation with a full width at half maximum duration of 10 ns was incident at an angle of about 80°to the surface normal on the ice surface at a fluence Ͻ0.1 mJ cm −2 pulse −1 . O͑ 3 P J=2,1,0 ͒ atom products were subsequently ionized at a distance of 4 mm ͑2 mm for OH͒ from the substrate surface by the ͑2+1͒ REMPI transition via the O͑ 3 P J − 3 P J ͒ transition at 225.6-226.4 nm, 24 and collected with a small mass spectrometer aligned perpendicular to the ice surface.…”
Section: Methodsmentioning
confidence: 99%
“…2 is uptake of gaseous N 2 O 4 on the surface and its isomerization to surface asymmetric ONONO 2 . This isomerization is known to occur in solid matrices at low temperatures or high pressures, on ice and in solution, 101,[135][136][137][138][139][140][141][142][143][144][145][146][147][148][149][150] (although one study 151 observed only the symmetric form of N 2 O 4 on ice films). Koel and coworkers [148][149][150]152 proposed that this isomerization occurs via the free O-H groups on amorphous ice, and it is possible that a similar process occurs in the thin films studied here.…”
Section: Mechanisms and Modelsmentioning
confidence: 99%
“…167 In the case of the NO 2 studies, Cheung et al 132 found no evidence for a reactive NO 2 complex at the interface. There is one report 151 …”
mentioning
confidence: 99%
“…ASW was prepared with the backfilling deposition of water vapor for 60 min onto an optically flat sapphire disk substrate, sputter coated with a thin polycrystalline film of Au͑111͒ cooled by liquid nitrogen at 90 K. The exposure was typically 1500 L ͑1 L=1ϫ 10 −6 Torr s͒. This exposure resulted in the formation of roughly 500 ML ͑monolayer͒ of H 2 O on the substrate if we adopt the reported experimental conversion factor of 1 ML deposition by 3 L exposure, 26 which is sufficiently thick to neglect the possible influence of reactions at the ASW/Au substrate interface and of any photoelectrons from the Au substrate. 4,5,27 For the concentrated H 2 O 2 photolysis experiments, a commercially available H 2 O 2 solution ͑30%͒ was concentrated in a glass container by vacuum distillation, and the H 2 O 2 / H 2 O vapor was deposited on ASW.…”
Section: A Apparatus and Preparation Of Icementioning
confidence: 99%